Practical issues in choosing a framework for resource assessment and management of Mediterranean and Black Sea fisheries - CADDY, J.F. (Mediterranean Marine Science, 2009)
Local context and practical constraints are important in deciding on assessment procedures for Mediterranean and Black Sea fisheries, and in formulating management measures that reflect the resource life history, fishery configuration and availability of data. A brief review of existing methods is provided, and a recommendation that practical approaches need to focus on developing the indicators and reference points appropriate for fisheries management decisions. In both the Black Sea and Mediterranean Sea proper, experience suggests environmental and ecosystem concerns must be given a high priority in the assessment process.